The Role of Influenza Vaccination in Pregnant Women: Benefits and Risks – an Integrative Review - Krukowska, Kamila; Krupa, Martyna; Krzyśkowska, Sylwia; Kulczykowska, Wiktoria; Kozińska, Anna; Krawiec, Laura (Quality in Sport, 2026)
Background. Influenza is one of the most common seasonal viral infections and poses a significant risk of complications, especially for pregnant women. Due to immunological and physiological changes, pregnant women aremore susceptible to severe influenza and adverse pregnancy outcomes. Annual influenza vaccinations are an effective preventive measure; however, vaccination rates remain low, despite recommendations from the World Health Organization (WHO). Aim. The aim of this study was to review the literature on the efficacy and safety of influenza vaccinations in pregnant women and to assess their impact on maternal and fetal health. Material and methods. A literature review (2019–2024) was conducted in PubMed, focusing on influenza vaccination in pregnancy. An integrative approach was used to assess the risk–benefit balance for maternal and fetalhealth. Results. Research findings suggest that vaccination significantly reduces the risk of influenza infections in both mothers and their newborns, and lowers the incidence of pregnancy complications, such as preterm birth and lowbirth weight. No significant risks associated with congenital defects or other adverse health effects for the fetus have been identified. Conclusions. The analysis highlights the positive balance between the benefits and risks of influenza vaccination during pregnancy, supporting the need for widespread recommendations in this high-risk group.